Molecular And Genetic Mechanisms Of Cardiovascular Pathology In Patients With Rheumatoid Arthritis - Zarangis Kamolovna Tairova; Gulandom Zikriyayevna Shodikulova (Journal of Advanced Zoology, 2024)
Annotation. Rheumatoid arthritis is a disease where hereditary predisposition is associated with the activation of innate immunity, the HLA system, cytokine networks and others. The formation of substances in the body that have pro- and anti-inflammatory effects can be influenced by single nucleotide polymorphisms of a variety of genes, being one of the most frequent causes of changes in their sequence. Given the fact that the inflammatory process plays a significant role in the development of RA and atherosclerosis, also single-nucleotide polymorphisms may be involved in the development and progression of these diseases, which should be taken into account when identifying groups of high cardiovascular risk. Purpose: Based on the analysis of molecular genetic features, to identify structural and functional changes in the cardiovascular system, as well as to optimize early diagnosis of cardiovascular pathology in RA patients. Materials and methods. 100 patients of the main group and 30 individuals of the control group were examined for VEGF gene C936T and MMP 9 gene C1562T. Among them, there were 80 females (80%) and 20 males (20%). The median age was 48 years [41; 54] and the disease duration was 5 years [3; 8]. The control group included 30 practically healthy individuals comparable in age to the sample of RA patients. There were 21 (70%) women and 9 (30%) men. The mean age of women was 42.67±7.64 years. Results. The allele frequency of VEGF C936T (rs3025039) gene differs in different population groups, therefore it is considered necessary to conduct area-based studies. Heterozygosity in Caucasoid and Mongoloid populations varies from 12.5% to 42% worldwide; in a genotype study of the Uzbek population in Samarkand region, heterozygosity was 63%. The high degree of heterozygosity for this polymorphism makes it the most promising for further analysis of associations with the development of multifactorial diseases. Conclusions. The molecular genetic markers, allele T and genotype TT of VEGF 936 (rs3025039) and MMP9 1562 (rs3918242) genes detected in RA patients are associated with increased cardiovascular risk in rheumatoid arthritis.